L'aurora della psicologia morale. La psicologia morale di Nietzsche e alcune recenti indagini empiriche - Francesco Margoni (Rivista Internazionale di Filosofia e Psicologia, 2019)
Comparing Nietzsche’s moral psychology and the social intuitionist approach to moral judgment proposed by Jonathan Haidt, this paper reveals remarkable similarities between the two models. It also clarifies what implications Nietzsche drew from his description of human psychology and the perspective changes these entail for understanding ourselves as “moral beings”.